Rodent-Borne Zoonotic Viruses in Southeast Asia - Blasdell Kim; Herbreteau Vincent; Henttonen Heikki; Phonekeo Darouny; Hugot Jean-Pierre; Buchy Philippe (Agriculture and Natural Resources, 2009)
Arenaviruses and hantaviruses circulate among the rodent populations of southeast Asia, and can occasionally be transmitted to humans. The latter virus has been identified in human patients in southeast Asia, although the former has not. The case fatality rate due to hemorrhagic fever with renal syndrome (HFRS), caused by hantaviruses and carried by murine rodents, varies between 2–12%, while the case fatality rate due to the arenaviral lymphocytic choriomeningitis virus (LCMV) is lower than 1%. Great care must be taken to avoid infection in pregnant women by LCMV, where serious complications can occur. At present, treatment other than supportive therapy is unavailable for LCMV. A range of vaccines exists in Asia, or are under development for the prevention of hantavirus infection, while ribavirin can help in the early phase of an acute illness. With changing climates and land use and rapidly increasing globalization, it is likely that the situation regarding these zoonotic viruses will change, resulting in an increase in human infections. Few studies have been carried out in this region, particularly in terms of LCMV. More are needed to establish the rates of infection by these agents (and for other potential rodent-borne zoonoses), both in their rodent hosts and in humans, so that they can be used as a baseline to monitor any changes that may occur.